Zero-profile Anchored Spacer Reduces Rate of Dysphagia Compared With ACDF With Anterior Plating. Issue 5 (June 2015) - Hofstetter, Christoph P.; Kesavabhotla, Kartik; Boockvar, John A.
Abstract : Study Design: Retrospective cohort study. Objective: To study clinical and radiologic outcomes after anterior cervical discectomy and fusion (ACDF) using a zero-profile anchored spacer compared with a standard interposition graft with anterior plating. Summary of Background Data: Anterior plating increases fusion rates in ACDF but is associated with higher rates of postoperative dysphagia. Reduction of plate thickness or zero-profile fixation of the interposition graft have been suggested to decrease the incidence of postoperative dysphagia. Methods: Retrospective cohort study of 70 consecutive patients of whom the first 35 patients underwent ACDF with anterior plating and the remaining patients received an LDR device. Patient demographics, operative details, neurological impairment, complications, and radiographic imaging were reviewed. Dysphagia occurring in the immediate postoperative period and lasting for >3 months was recorded. Results: Both the zero-profile anchored spacer and a standard interposition graft with anterior plating resulted in improvement of neurological outcome at a mean follow-up time of 13.9 months. Fusion rates were found to be similar between ACDF with anterior plating (96.0%) and LDR (95.2%). Evaluation of postoperative radiographs revealed significantly more swelling of the prevertebral space (20.4±0.9 mm) after implantation of an anterior locking plate compared with a zero-profile device (15.6±0.7 mm, P <0.001). This difference remained significant at 6-month follow-up ( P =0.035). Seven patients (20%) with ACDF and plating complained about swallowing difficulties beyond 3 months compared with only 1 patient with the LDR device ( P =0.027). The severity of dysphagia was mild in all but 2 patients. Both patients with moderate and severe swallowing difficulties had undergone ACDF with anterior plating. Conclusions: Zero-profile anchored spacers lead to similar clinical and radiographic outcomes compared with ACDF with plating and may carry a lower risk of postoperative dysphagia.